'Vespasianus Militaris': profile of a Roman commander (27-69 AD) - Tiago Maria Líbano Monteiro Rocha e Melo (Espacio, Tiempo y Forma. Serie II, Historia Antigua, 2025)
The overall scholarly consensus portrays Vespasian as an effective and successful commander. However, it is a conclusion that seems to either be taken for granted, or else placed at the feet of those which Vespasian selected to surround him (i.e.: the partes flauianae) focusing on his accession to power in Rome. This paper seeks to contribute to the study of Vespasian by presenting a qualitative analysis of his military career through the lens of four Roman concepts, namely: gloria, labor militaris, uirtus and auctoritas. This approach will give us a more complete account for Vespasian’s military success that the modern scholarly world lacks. Additionally, it will be argued that there was a difference in perspective regarding Vespasian between Roman political elites and the soldiers, challenging his alleged bad reputation. Finally, all of the above will permit a re-evaluation of the soldiers’ willingness to follow Vespasian in his bid for power in Rome.